An environmental court in action function, doctrine and process - Preston, Brian J.; Fisher, Elizabeth (Oxford Hart, 2022)
This book provides a critical assessment of the New South Wales Land and Environment Court (NSWLEC). Effective adjudication has become a key consideration for environmental lawyers. One of the most important questions is whether environmental law frameworks need their own courts, with the conclusion being: yes they do. Here, a pioneer of such a court, the NSWLEC is forensically examined to see what it might teach other such courts. Showing a court 'in action' it suggests models that practitioners and policy makers might follow. It also speaks to the environmental law scholars, setting out a conceptual framework for studying such courts as legal institutions"--The Land and Environment Court of New South Wales and the Transnationalisation of Climate Law: The Case of Gloucester Resources v Minister for Planning--Transnational Dimensions of the Land and Environment Court of New South Wales--The International Outreach of the Land and Environment Court of New South Wales: Diffusion in India--Biodiversity and the Land and Environment Court of New South Wales--
The Many Facets of a Cutting-Edge Court: A Study of the Land and Environment Court of New South Wales / The Hon Justice Brian J Preston -- From Reactive to Proactive Decision-Making by the Land and Environment Court of New South Wales / Douglas Fisher -- The Place of the Land and Environment Court in the Planning System of New South Wales / Leslie Stein -- The Land and Environment Court of New South Wales and the Transnationalisation of Climate Law: The Case of Gloucester Resources v Minister for Planning / Jacqueline Peel -- Transnational Dimensions of the Land and Environment Court of New South Wales / Ben Boer -- The International Outreach of the Land and Environment Court of New South Wales: Diffusion in India / Gitanjali Nain Gill -- Biodiversity and the Land and Environment Court of New South Wales / Paul Adam -- Environmental Principles and the Construction of a New Body of Legal Reasoning / Eloise Scotford -- The Land and Environment Court of New South Wales and the Recognition of Indigenous Peoples' Environmental Rights / Megan Davis -- The Administrative Law Expertise of the Land and Environment Court of New South Wales / Elizabeth Fisher -- Ecocentrism and Criminal Proceedings for Offences against Environmental Laws / Rob White -- You Can Only Keep Something by Giving it Away / Tim Bonyhady -- 'Please Come In': Access to Justice and the Development of Jurisprudence in the Land and Environment Court of New South Wales / Jeff Smith and Sue Higginson -- Alternative Dispute Resolution in the Land and Environment Court of New South Wales / Mary Walker OAM -- The Land and Environment Court of New South Wales: Normative Legitimacy and Adjudicative Integrity / Ceri Warnock -- Afterword: Law in Unexpected Places / Elizabeth Fisher
Includes bibliographical references and index
Keywords: New South Wales -- Land and Environment Court; Courts of special jurisdiction; Courts of special jurisdiction -- Australia -- New South Wales; Environmental law -- Australia -- New South Wales